Telluride-Based Materials: A Promising Route for High Performance Supercapacitors - Khan, Abdul Jabbar; Sajjad, Muhammad; Khan, Shaukat; Khan, Muhammad; Matten, Abdul; Shah, Syed Shaheen; Arshid, Numan *; He, Liang; Ma, Zeyu; Gao, Ling; Zhao, Guowei (John Wiley & Sons, 2023)
As supercapacitor (SC) technology continues to evolve, there is a growing need for electrode materials with high energy/power densities and cycling stability. However, research and development of electrode materials with such characteristics is essential for commercialization the SC. To meet this demand, the development of superior electrode materials has become an increasingly critical step. The electrochemical performance of SCs is greatly influenced by various factors such as the reaction mechanism, crystal structure, and kinetics of electron/ion transfer in the electrodes, which have been challenging to address using previously investigated electrode materials like carbon and metal oxides/sulfides. Recently, tellurium and telluride-based materials have garnered increasing interest in energy storage technology owing to their high electronic conductivity, favorable crystal structure, and excellent volumetric capacity. This review provides a comprehensive understanding of the fundamental properties and energy storage performance of tellurium- and Te-based materials by introducing their physicochemical properties. First, we elaborate on the significance of tellurides. Next, the charge storage mechanism of functional telluride materials and important synthesis strategies are summarized. Then, research advancements in metal and carbon-based telluride materials, as well as the effectiveness of tellurides for SCs, were analyzed by emphasizing their essential properties and extensive advantages. Finally, the remaining challenges and prospects for improving the telluride-based supercapacitive performance are outlined.